Law and legal culture in Anglo-Saxon England - Rabin, Andrew ca. 20./21. Jh. (History compass, 2020)
The reception and study of pre-Conquest legal texts can never be fully disentangled from the historical and political contexts within which they transpired. Indeed, the historiography of early English law has been shaped as much by the desires, prejudices and ideological commitments of its historians as it has by the texts themselves. Modern scholarship has not ‘risen above’ its predecessors but is instead guided (and at times governed) by the history of the laws' reception from the post-Conquest period onwards. The boundaries of the Old English legal corpus are far more fluid than often recognized and its survival has been determined by political forces and social trends that reshaped and recontextualized it in ways that those involved in its composition may not have intended or even understood. To better understand how the modern study of Anglo-Saxon legal culture has been and continues to be shaped by these influences, this article first outlines a brief history of the reception of early English legal texts from the Conquest onwards before turning to a review of the major themes and trends in contemporary scholarship. As will become apparent, for modern scholars, the interpretation of legal records, the historical narrative they appear to construct and even the parameters of the corpus itself have all been shaped by the nostalgia, biases and scholarly priorities of their predecessors.